Annual asymmetry in thermospheric density: Observations and simulations. Issue 5 (15th May 2013) - Lei, Jiuhou; Dou, Xiankang; Burns, Alan; Wang, Wenbin; Luan, Xiaoli; Zeng, Zhen; Xu, Jiyao
Abstract: [1] In this paper, the Challenging Minisatellite Payload (CHAMP) and Gravity Recovery and Climate Experiment (GRACE) observations during 2002–2010 are utilized to study the variation of the annual asymmetry in thermospheric density at 400 km under low solar activity condition ( F 10.7 = 80) based on the method of empirical orthogonal functions (EOFs). The derived asymmetry index (AI) in thermospheric density from the EOF analysis shows a strong latitudinal variation at night but varies a little with latitudes in daytime. Moreover, it exhibits a terdiurnal tidal signature at low to middle latitudes. The global mean value of the AI is 0.191, indicating that a 47% difference in thermosphere between the December and June solstices in the global average. In addition, the NCAR Thermosphere‐Ionosphere Electrodynamics Global Circulation Model (TIEGCM) is used to explore the possible mechanisms responsible for the observed annual asymmetry in thermospheric density. It is found that the standard simulations give a lower AI and also a weaker day‐to‐night difference. The simulated AI shows a semidiurnal pattern in the equatorial and low‐latitude regions in contrast with the terdiurnal tide signature seen in the observed AI. The daily mean AI obtained from the simulation is 0.125, corresponding to a 29% December‐to‐June difference in thermospheric density at 400 km. Further sensitivity simulations demonstrated that the effect of the varying Sun‐Earth distance between the December and June solstices is the main process responsible for the annual asymmetry in thermospheric density, while the magnetic field configuration and tides from the lower atmosphere contribute to the temporal and spatial variations of the AI. Specifically, the simulations show that the Sun‐Earth distance effect explains 93% of the difference in thermospheric density between December and June, which is mainly associated with the corresponding changes in neutral temperature. However, our calculation from the density observations reveals that the varying Sun‐Earth distance effect only accounts for 67% of the December‐to‐June difference in thermosphere density, indicating that the TIEGCM might significantly underestimate the forcing originating from the lower atmosphere. Key Points: First attempt to address thermospheric annual asymmetry Solar flux difference due to varying Sun‐Earth distance is the main cause Forcing originating from the lower atmosphere should be important as well